The Effects of Increased Maxillary Canine Bracket Angulation on Tooth Movement and Alignment Efficiency: A Prospective Clinical Study - Murat Türedi; Sabahat Yazıcıoğlu (Galenos Yayinevi, 2022)
Objective: This study aimed to evaluate the effects of a 10° angulation of a maxillary canine (Mx3) bracket on Mx3 and maxillary central incisor (Mx1) tooth movements and alignment efficiency in treatments involving maxillary premolar extraction.Methods: This split-mouth study included 29 individuals in a +10° angulation study group and a 0° angulation control group. The initial (T0) and 12th week (T1) orthodontic models were prepared and digitized with a three-dimensional scanner and superimposed using the OrthoAnalyzer analysis program. The movements of Mx3 and Mx1 were measured, and the alignment efficiency was assessed using Little's Irregularity Index. The Shapiro-Wilk test was used to test the data for a normal distribution. T1 and T0 measurements within the group and T1 and T0 differences between groups were compared using a paired samples t-test. The significance level was set to P < .05.Results: The linear movements of Mx3 in the distal direction significantly increased, and Little's Irregularity Index values statistically significantly decreased in both groups. Distal movements of Mx3 were significantly higher in the control group than in the study group (P < 0.01 and P < 0.05). The movements of Mx1 and Little's Irregularity Index measurements did not show statistically significant differences between the groups (P > 0.05).Conclusion: A +10° Mx3 bracket angulation increased the inclination of Mx3 to the mesial, but it decreased the Mx3 distal linear movement and the retraction of Mx1, with no difference in terms of alignment efficiency between the + 10° and 0° Mx3 bracket angulations.